Effects of Normobaric Hypoxia on Matched-severe Exercise and Power-duration Relationship - Sousa, Ana Catarina; Millet, Gregoire P.; Viana, João; Milheiro, Jaime; Reis, Vítor (International Journal of Sports Medicine, 2021)
We investigated the effects of hypoxia on matched-severe intensity exercise and on the parameters of the power-duration relationship. Fifteen trained subjects performed in both normoxia and normobaric hypoxia (FiO2=0.13, ~3000 m) a maximal incremental test, a 3 min all-out test (3AOT) and a transition from rest to an exercise performed to exhaustion (Tlim) at the same relative intensity (80%∆). Respiratory and pulmonary gas-exchange variables were continuously measured (K5, Cosmed, Italy). Tlim test’s V̇O2 kinetics was calculated using a two-component exponential model. V̇O2max (44.1±5.1 vs. 58.7±6.4 ml.kg-1.min-1, p<0.001) was decreased in hypoxia. In Tlim, time-to-exhaustion sustained was similar (454±130 vs. 484±169 s) despite that V̇O2 kinetics was slower (τ1: 31.1±5.8 vs. 21.6±4.7 s, p<0.001) and the amplitude of the V̇O2 slow component lower (12.4±5.4 vs. 20.2±5.7 ml.kg-1.min-1, p<0.05) in hypoxia. CP was reduced (225±35 vs. 270±49 W, p<0.001) but W’ was unchanged (11.3±2.9 vs. 11.4±2.7 kJ) in hypoxia. The changes in CP/V̇O2max were positively correlated with changes in W’ (r = 0.58, p<0.05). The lower oxygen availability had an impact on aerobic related physiological parameters, but exercise tolerance is similar between hypoxia and normoxia when the relative intensity is matched despite a slower V̇O2 kinetics in hypoxia.
Keywords: exercise-to-exhaustion; critical power; hypoxia; W'